Tonal Poetry, Bop Aesthetics, and Jack Kerouac’s Visions of Gerard - James J. Donahue (European Journal of American Studies)
In the following article, I will attempt to outline a new reading methodology for Beat fiction, based on some of the principles of bop aesthetics. This reading understands fiction—especially Beat fiction—as an aural art, as opposed to merely a textual phenomenon (and so considers fiction in much the same way that poetry and music are often considered). Jack Kerouac composed his novel Visions of Gerard in 1956 (released in 1963), the same year Charles Mingus released his classic album Pithecanthropus Erectus. I contend that by reading Kerouac’s novel in terms of Mingus’s methods of composition as recorded on that album, we can more clearly hear the influence of jazz music on Kerouac’s prose; as such, we can better understand the means by which jazz music became important as a compositional method and not just as a theme for Kerouac’s novels. Further, becoming more attuned to the means by which Kerouac composed his fiction as an aural soundscape—how he was sensitive not just to the words themselves but to the sounds that comprise those words and their relationships—we can better appreciate the various ways that Kerouac imbued his novels with aural qualities that emphasized the ideas and emotions raised and/or engaged by the narratives.